Konstruksi Inovasi Pembelajaran Dalam Membangun Kesiapan Bersekolah Anak Usia Dini - Regita Musfita; Ratna Dwi Nurcahyani (Jurnal El-Audi, 2025)
School readiness is often understood merely as children's academic readiness, leading learning innovations in early childhood education to focus more on individual achievement rather than on fostering learning experiences that support a successful transition to primary school. This condition reflects the limited research examining how learning innovations are constructed as pedagogical processes to build comprehensive school readiness. This study aims to analyze the construction of learning innovations in building school readiness at TK Cendani Bandung. Employing a qualitative approach with a case study design, this research involved one school principal, one classroom teacher, and 18 children from Group B aged 5–6 years. Data were collected through non-participant observation, in-depth interviews, and documentation review, and subsequently analyzed using Grounded Theory stages, including open coding, axial coding, and selective coding. The findings indicate that learning innovations are constructed through four dimensions: exploratory, contextual, collaborative, and habituative. These four dimensions are integrated to shape learning experiences that foster curiosity, critical thinking skills, social adaptation, self-regulation, independence, and responsibility as the foundation of school readiness. The study expands the understanding that school readiness is not solely determined by academic competence but is constructed through holistic learning experiences.